Musicoterapia receptiva com a mesa lira no período de desintoxicação em dependentes químicos: estudo randomizado controlado - Teixeira, Andressa Toledo (2019)
During the process of abstinence from chemical dependence, the user presents some common symptoms to any type of drug, such as anxiety, depression, hypomania / mania. In most cases, treatment is drug-associated with non-drug therapies. The receptive experience is a technique of music therapy and vibroacoustic therapy through Mesa Lira (ML) is one of the modalities of receptive music therapy used in the treatment of physical and emotional illness. Objective: To investigate whether Receptive Music Therapy with mesa lira can reduce drug addiction anxiety levels in an internment regime detox program, by comparing two distinct protocols for music therapy intervention. Methodology: Controlled randomized clinical trial in male and female drug users from 18-year-old on an average hospitalization period of 28 days at the Detoxification Program at Casa de Eurípedes institution, in Goiânia, Goiás, Brazil, with four groups, two intervention (GMT-A: five sessions of music therapy (MT) on consecutive days; GMT-B: five sessions of music therapy on alternate days) and two controls (GCA and GCB). The groups participants were submitted to a sociodemographic questionnaire, Drug Temptation Scale (ESTUD), Drug Abstinence Self-efficacy Scale (EAAD), Trait Anxiety Inventory and Status Anxiety Inventory to assess Anxiety Level (IDATE). Specifically to the participants of the music therapy groups, a scale of relaxation level (NR) subjective rating on Mesa Lira, Body Vibration Perception, Music Therapeutic Questionnaire (QMT) and Subjective Impression of the Subject (ISS) were applied. Results and Discussion: 40 subjects were included, 20 (19 men and 1 woman) for stage “A” and 20 (19 men and 1 woman) for stage B. Mean age: GMT-A (38.0), GC-A (32.2), GMT-B (43.6) and GC-B (41.4). In the intragroup evaluation, comparing pre and post MT sessions, both groups presented results with statistical significance for IDATE-E in the fourth session for GMT-A (ρ = 0.064) and in the third session of MT (ρ = 0.012), NR presented significance levels for all sessions in both groups. Intergroup evaluation points to better results for GMT-B. The evaluation between intervention groups and their respective controls shows significant results for GMT-A (ESTUD ρ = 0.056 and EAAD ρ = 0.038). Reports from intervention group participants (ISS) confirm the quantitative findings. Regarding the aspect of treatment dropout / internment period, this was lower among participants in the intervention groups. Conclusion: Music therapy, as a complementary treatment, worked to improve anxiety symptoms, decrease the temptation to use the drug and strengthen during abstinence. The results are relevant, as they reflected in the patient's better adherence to the treatment as a whole, since dropout is a problem for this clientele. We hope this study can contribute to the strengthening of music therapy as a complementary treatment of choice for this complex area. We suggest that further research be conducted with music therapy in chemical dependence, aiming to expand knowledge and, with this, strategies for treatment and prevention of drug abusive use.